DESKRIPSI MODAL SOSIAL MASYARAKAT DI DESA EKOWISATA TAMBAKSARI (Studi Kasus Desa Tambaksari, Kecamatan Purwodadi, Kabupaten Pasuruan, Jawa-Timur) - Rukavina Baksh (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The objective of the study was to descriptively determine the social capital of the community in the Tambaksari Village. There were as many as 170 people involved in the study. The data were then analyzed using descriptive statistics. The results showed that the local community of Desa Tambaksari agreed that networking and norms had been strongly implemented, while trust and paticipation were implemented at medium level in the development of ecotourism. Therefore, trust and participation need to be improved. Key Words: Ecotourism, social capital.